Amateur Sports Clubs’ Social Media Usage as a Tool for Online Marketing - ADAŞ, Selda KOCAMAZ; ÇİMEN, Zafer; DURSUN, Mücahit (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
The purpose of this research was to explore the opinions of amateur sports clubs social media usage as an online marketing tool. This qualitative research was designed as a phenomenological study and participants were selected with convenience sampling and maximum variation sampling both of which are among purposive sampling techniques. Participants consisted of seven individuals selected from the sports club managers responsible for the social media platforms of amateur sports clubs operating in different sports branches in Ankara. Data were collected using a semi-structured interview form prepared by the researchers and analyzed with content analysis method. In the study, according to analyzed results, four themes and eleven categories related to these themes were explored. The themes consisted of the benefits of using social media entitled "advantages", the selection of social media platforms entitled "popularity", the experiences in reaching the target group entitled "change" and the method of using social media entitled "professionalization". In conclusion, the study revealed that even though sports clubs which became aware of the impact and power of social media used it for communicating, sharing information and interacting with supporters as well as marketing, they fell short in terms of the efficient use of the information and findings obtained during this process.